Anti-Allergic Properties of Propolis: Evidence From Preclinical and Clinical Studies - Kong Yen Liew; Nurain Irdayani Kamise; Hui Ming Ong; Poi Yi Aw Yong; Fahmida Islam; Ji Wei Tan; Chau Ling Tham (Frontiers in Pharmacology, 2022)
Allergic diseases are a global health burden with increasing prevalence. Side effects of available medications (antihistamines and steroids), lack of patients’ perceived effectiveness and high cost of biologic therapies (omalizumab) are challenges to the clinical management of allergic diseases. As allergy symptoms persist for a long time, complementary and alternative medicine (CAM) such as propolis may be considered a potential prophylactic or therapeutic option to avoid long-term medication use. Propolis is a natural resinous substance produced by bees. Although propolis is well known to possess antioxidant, antimicrobial, and anticancer properties, its anti-allergic potential is not fully explored. Several preclinical studies demonstrated the therapeutic effects of propolis extracts against allergic inflammation, asthma, allergic rhinitis, atopic dermatitis, and food allergy, which may be partly attributed to their inhibitory effects on the activation of mast cells and basophils. Clinically, the consumption of propolis as a supplement or an adjunct therapy is safe and attenuates various pathological conditions in asthma. Such an approach may be adopted for atopic dermatitis and allergic rhinitis. Although flavonoids (chrysin, kaempferol, galangin, and pinocembrin) and cinnamic acid derivatives (artepillin C and caffeic acid phenethyl ester) can contribute to the anti-allergic activities, they may not be present in all propolis samples due to variations in the chemical composition. Future studies should relate the anti-allergic activity of propolis with its chemical contents. This mini-review summarizes and discusses existing preclinical and clinical studies reporting the anti-allergic activities of propolis to provide insights into its potential applications in allergic diseases.